The Clinical Difference between Gabapentin and Pregabalin: Data from a Pilot Comparative Trial - Gammoh, Omar; Al-Smadi, Ahmed; Shawagfeh, Mohammad Q.; Abadi, Thani; Kasawneh, Jawad; Malkawi, Sukaina; Zein, Sima (Reviews on Recent Clinical Trials, 2021)
Background: Similar anticonvulsants, such as gabapentin and pregabalin are recommended in neuropathic pain management, however little is known about their clinical differences in cases of low back pain. This paper aims to highlight some of the possible clinical differences between gabapentin and pregabalin in low back pain. Methods: Patients with moderate to severe low back pain were recruited. Eligible patients were randomised to receive either pregabalin (300 mg/day)or gabapentin (800 mg/day) for six weeks. The primary outcome measure was pain intensity according to the Visual Analogue Score (VAS) at baseline and at six weeks. The secondary outcome measures were: anxiety, insomnia, fatigue and the self-rated (GCI), measured at baseline, second, fourth, and the sixth week. Results: A total of 64 patients, pregabalin group (n=28), gabapentin group (n=36) completed the study. While pregabalin group showed a significantly lower pain score (p=0.039). The gabapentin group showed significant improvement in anxiety (p=0.001), insomnia (p=0.001), general fatigue (p=0.009), physical fatigue (p=0.001), reduce activity (p=0.001), and mental fatigue (p=0.014) higher than that of pregabalin. No difference in (GCI) was seen at six weeks. Conclusion: This is the first trial aimed at comparing gabapentin with pregabalin in NLBP. Although the results are preliminary, in our pilot study pregabalin was found to be superior in pain reduction, gabapentin demonstrated better effect on anxiety, insomnia and fatigue symptoms. The results are preliminary and studies with a larger sample size are still required.
Keywords: anticonvulsants